2015
DOI: 10.1242/jeb.116327
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence that litter size imposes an oxidative challenge to offspring

Abstract: The post-natal environment in which young develop can substantially impact development, adult phenotype and fitness. In wild mice, competition among litter-mates affects development rate and adult behaviour. We manipulated post-natal litter size in a cross-fostering design to investigate the effects of enlarged and reduced litter sizes on sexual signalling, oxidative stress and the links between them. Oxidative stress causes somatic damage that can limit reproductive success and lifespan, and is predicted to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 71 publications
1
12
0
Order By: Relevance
“…An additional impact may be experienced by their offspring. We found that the offspring raised in reduced and enlarged litters differed significantly in their body mass, and poor early nutrition has been previously linked to impairment of performance and reduced survival in several species (Gibson et al, 2015;Plumel et al, 2014). In line with these previous suggestions, we found that pup mass at weaning was reduced in females from enlarged litters compared with females from reduced Day of lactation at which measurements were taken is indicated for each variable.…”
Section: Discussionsupporting
confidence: 87%
“…An additional impact may be experienced by their offspring. We found that the offspring raised in reduced and enlarged litters differed significantly in their body mass, and poor early nutrition has been previously linked to impairment of performance and reduced survival in several species (Gibson et al, 2015;Plumel et al, 2014). In line with these previous suggestions, we found that pup mass at weaning was reduced in females from enlarged litters compared with females from reduced Day of lactation at which measurements were taken is indicated for each variable.…”
Section: Discussionsupporting
confidence: 87%
“…At 13 weeks of age, half of the female and male offspring from the novel male and familiar male treatment groups were culled humanely by cervical dislocation, and the liver, kidney, heart and gastrocnemius muscle were quickly removed, snap‐frozen in liquid nitrogen and stored at −80°C. To assess oxidative stress in the mice, two biomarkers of oxidation including protein thiol content and aconitase enzyme activity were analysed in each of the tissues (Gibson, Garratt & Brooks, ). Both of these biomarkers correlate negatively with oxidative stress.…”
Section: Methodsmentioning
confidence: 99%
“…However, despite large litter sizes, we observed that HA pups maintained similar growth rates to LA pups. While mothers in our study were fed ad libitum, larger litter sizes should still increase intra-litter competition for milk [56]. If HA pups are nutrient limited owing to increased competition from litter mates, then suppressing energetically costly thermogenesis may help them recoup some of their energetic costs in favour of maintaining growth rates even in normoxia.…”
Section: (C) Adaptive Benefits Of Delayed Development Of Homeothermicmentioning
confidence: 95%